(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article talks about different approaches to the development of students’ computational thinking with the help of specific sciences, the analysis of various definitions given to it, and the methodological foundations of developing computational thinking. Evolutionary stages of development of computer thinking, cognitive approaches to education, computational thinking are also presented. In the study of the science of "Digital control systems", its cognitive development was analyzed taking into account the possibilities.